HUBUNGAN ANTARA HARGA DIRI DENGAN KECENDERUNGAN NARSISISTIK PADA SISWA SMA KRISTEN 1 SALATIGA YANG MENGGUNAKAN JEJARING SOSIAL INSTAGRAM - Lius Devita Cecillia (Jurnal Psikohumanika, 2017)
The social phenomenon of social network such as instagram can be easily found recently. The instagram users is a group with unique characteristics such as has the tendency of narcissistic and has unique self-esteem also. The aim of this research is to test empirically the connection of the tendency to be narcissistic on instagram users, based on self-esteem point of view. Proposed hypothesis such as there is a negative connection between self-esteem and the tendency to be narcissistic on instagram users. For them, who have lower self-esteem, the higher tendency to be narcissistic and vice-versa. Using subject research high school cristian 1 class XI student Salatiga using sampling techniques saturated. The research is quantitative in nature with Narcissistic Tendency Scale and Self-esteem Scale as variables. Both scales were distributed in high school Cristian 1 Salatiga to research subjects with incidental sampling method. The total of respondents who were succeeded to be gathered were 70 people. Based on data analysis, it is shown that r = -0.004 with p<0.05. It means very significant negative connection between self-esteem and the tendency to be narcissistic on instagram users. Thus, the analysis result provided the basis for the accepted hypothesis.